CORRELATION BETWEEN GENERAL CRIMINAL PROVISIONS AND SPECIAL CRIMINAL PROVISIONS CONCERNING THE CRIMINAL ACTION OF DEFENSE - Yohanis Sudiman Bakti (Sekolah Pascasarjana Universitas Swadaya Gunung Jati, 2023)
The purpose of this study is to find out how the general criminal and special criminal arrangements regarding the criminal act of defamation. This research uses an empirical juridical approach. The juridical approach is used to analyze various laws and regulations related to the implementation of the criminal defamation settlement process. Meanwhile, the empirical approach is used to analyze law which is seen as patterned social behavior in people's lives that always interact and relate to social aspects. The provisions for criminal acts of defamation in the Information and Electronic Transactions Law in its implementation refer to the legal provisions in the Criminal Code Articles 310 and 311 of the Criminal Code and the Electronic Information and Transactions Act Article 27 paragraph (3), Article 45 paragraph (1). This was emphasized because it was the result of an amendment to the provisions of Article 27 paragraph (3) which was considered by some people to be a rubber article because it was not accompanied by an explanation of the article regarding the measure of being said to be defamation.